Long-term effects of anterior cruciate ligament reconstruction on neuromuscular asymmetries in elite alpine ski racers - Jordan, M. J.; Maurer, C.; Aagaard, P.; Herzog, W. (Abstractband der 6. Internationalen Konferenz Wissenschaft und Skisport. 14.-19. Dezember 2013, St. Christoph am Arlberg, Österreich, 2013)
The long-term effects of ACL reconstruction (ACL-R) in elite ski racers are unknown yet neuromuscular asymmetries implicated in re-injury may persist. ACL reinjury occurs frequently in elite ski racers [4] and a deeper understanding of the neuromuscular changes with ACL-R may improve return to snow outcome. The purpose of this study was to measure between-limb asymmetry in muscle mass, quadriceps/hamstrings strength, vertical ground reaction force (GRF) production in countermovement jumping (CMJ), and quadriceps/hamstrings muscle activity in the CMJ in elite ski racers with a history of ACL-R. ACL-R skiers (AS) were hypothesized to show greater asymmetry in these parameters compared to healthy skiers (HS).